Answer:
(- p) × (- p) × (- p)
Step-by-step explanation:
(-p)³
(- p) × (- p) × (- p)
For this case we must simplify the following expression
![-5 + 7q + (- 5q) + (- 9q)](https://tex.z-dn.net/?f=-5%20%2B%207q%20%2B%20%28-%205q%29%20%2B%20%28-%209q%29)
We know that, by definition:
![+ * - = -](https://tex.z-dn.net/?f=%2B%20%2A%20-%20%3D%20-)
So, rewriting the expression we have:
![-5 + 7q-5q-9q =](https://tex.z-dn.net/?f=-5%20%2B%207q-5q-9q%20%3D)
We add similar terms taking into account that:
- Equal signs are added and the same sign is placed.
- Different signs are subtracted and the major's sign is placed:
![-5 + 2q-9q =\\-5-7q](https://tex.z-dn.net/?f=-5%20%2B%202q-9q%20%3D%5C%5C-5-7q)
Answer:
![-5-7q](https://tex.z-dn.net/?f=-5-7q)
Answer:
The third one
Step-by-step explanation:
A:
2t
t is the number of toys
b:
(p+12)/16
p is the price